Metrics in Arabic poetry - Manna, Hashim Saleh; al-Zu’bi, Basil Faisal Sa’ed; Zamri Arifin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study discusses the significance of metrics in Arabic poetry, its motives and reasons behind its creation. It also explains the controls, criteria measurements and accuracy of this metrics. In addition, it elaborates on what the result will be when a pause, or movement or a letter is accommodated or when the opposite happens. The study afterwards illustrates how al-Khalil Bin Ahmed founded this science relying solely on two symbols in the field of metrics and syllabification. The study also correlates the relation between prosody symbols and those used in computers. It also concentrates on the relation between meters and meanings, the significance of meters with regard to music, rhythm and tone. This study depended on original sources adopting the descriptive and analytical methods. Finally, the study came up to a group of conclusions and recommendations that are in line with the study results emanating from discussion, analysis, justification, and computation.